Evaluation of bis-cyclometalated alkynylgold(iii) sensitizers for water photoreduction to hydrogen. Issue 43 (6th October 2016) - Yu, Zhen-Tao; Liu, Xiao-Le; Yuan, Yong-Jun; Li, Yong-Hui; Chen, Guang-Hui; Zou, Zhi-Gang
Abstract : Gold(iii ) acetylide complexes actively catalyzed the light-driven evolution of hydrogen in water when using [Co(2, 2′-bipyridine)3 ]Cl2 or [Rh(4, 4′-di- tert -butyl-2, 2′-bipyridine)3 ](PF6 )3 as a H2 -evolved catalyst. Abstract : Well-defined gold sensitizers for hydrogen production from water remain extremely rare despite decades of interest, and are currently limited to systems based on ruthenium, iridium or platinum complexes. This report details the synthesis and characterization of a series of neutral cyclometalated gold(iii ) complexes of the type [(RC^N^CR)Au(CC–R′)] (R = H or tert -butyl group; R′ = aryl groups) that have been found to be good candidates to function as harvesting materials in light-induced electron transfer reactions. We established the efficacy of systems with these gold(iii ) complexes as photosensitizers (PSs) in the production of renewable hydrogen in the presence of [Co(2, 2′-bipyridine)3 ]Cl2 or [Rh(4, 4′-di- tert -butyl-2, 2′-bipyridine)3 ](PF6 )3 as a H2 -evolved catalyst and triethanolamine (TEOA) as a sacrificial electron donor in acetone–water solution. All complexes are active, and there is a more than threefold increase over other candidates in photocatalytic H2 generation activity. Under the optimal reaction conditions, hydrogen evolution took place through a photochemical route with the highest efficiency and with a turnover number (TON) of up to 1441.5 relative to the sensitizer over 24 hours. In the initial photochemical path, the reductive quenching of the excited gold(iii ) complex by TEOA due to the latter's greater concentration in the system followed by electron transfer to the catalyst species is proposed to be the dominant mechanism. A photo-to-H2 quantum yield of approximately 13.7% was attained when illuminated with monochromatic light of 400 nm. Such gold(iii ) complexes have demonstrated significant utility in solar-to-hydrogen reactions and thus represent a new effective class of light-harvesting materials. These results open possibilities for pursuing more efficient photosensitizers featuring gold(iii ) complexes in photocatalytic solar energy conversion.